2020
DOI: 10.15342/ijms.7.204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Disorders among Dentists in Casablanca’s Dental Center

Abstract: Introduction: Musculoskeletal disorders (MSDs) are the most common occupational pathologies among dentists around the world but studies are quite limited. The present study was carried out to investigate the prevalence of MSDs among dentists in Casablanca, Morocco.Methods: This was a cross-sectional descriptive study conducted among the medical staff (120 dentists) of casablanca’s Dental Center, part of the Ibn Rochd University Hospital, Morocco, over a period of 3 weeks from July 24, 2017 to August 11, 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Their results were similar to ndings of our meta-analysis. Several other studies conducted in countries outside Africa have shown comparable rates of MSDs in physiotherapists, dentists and nurses [34, [26], [23], [27], [22]. The reason for this could be that their work activities involve unnatural positions for a long period of time regardless of geographical distribution globally.…”
Section: Discussionmentioning
confidence: 93%
“…Their results were similar to ndings of our meta-analysis. Several other studies conducted in countries outside Africa have shown comparable rates of MSDs in physiotherapists, dentists and nurses [34, [26], [23], [27], [22]. The reason for this could be that their work activities involve unnatural positions for a long period of time regardless of geographical distribution globally.…”
Section: Discussionmentioning
confidence: 93%